Fabrication of Micron-Scale Cylindrical Tubes by Two-Photon Polymerization. (1st September 2016) - Bernat, T. P.; Campbell, J. H.; Petta, N.; Sakellari, I.; Koo, S.; Yoo, J.-H.; Grigoropoulos, C.
Abstract: Hollow cylindrical tubes grown directly from flat glass substrates as well as spherical glow-discharge-polymer substrates were made using two-photon polymerization. The tube diameters were as small as 10-μm outer diameter and 4- to 5-μm inner diameter, and lengths were as long as 450 μm. Such structures could conceivably be used as fill tubes on inertial confinement fusion capsules. Two resin materials were examined, giving tubes with different flexibilities. One resin was an organic-inorganic hybrid silicon-zirconium sol gel, the second being Ormocomp, a commercially available ultraviolet-curable material. The strength of attachment of the zirconium-based sol gel tubes to their substrates was measured to be around 100 MPa. The times measured to remove uncured resins from high-aspect-ratio tubes during the development process were several hours.